الإعفاء من المسؤولية الدولية في القانون الدولي - 'Ali Umar Miftah Midun; Ahmad Muhammad Husni (Universiti Sains Islam Malaysia, 2024)
This study discusses the important factors that prevent international obligations. The first of these is the consent of the countries. The breach of international law can always be resolved definitively if the parties involved in the international dispute consented to overcome it. The second factor is equal treatment. It means that it is the rights of the country involved in a hostile situation to reciprocate the hostility without having to bear the responsibility for its action in this situation. The third factor is the situation of emergency. The study is based on a sample of countries with relevant cases and aims to reinstate the fact that the regulations relating to international law are based on the consent of the involved countries. Thus, it is not plausible to punish a country that acted consensually towards another country, reciprocate hostility against the aggressor, and acted during the state of emergency. Inductive method is employed in this study to gather the relevant data and analyze it accordingly. The results of the study indicate the existence of certain illegal actions inflicted upon certain countries that are legalized due to the consent of the involved countries, situations during the state of emergency, or due to reciprocal actions. Therefore, a country should not be held responsible for any illegal actions that resulted from any of these afore-mentioned factors.